2012
DOI: 10.1080/15275922.2012.676598
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Assessment of Refined Tar-Based Sealers as a Source of Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Sediments

Abstract: Atmospheric deposition of particles and their subsequent transport by stormwater are a major source of polycyclic aromatic hydrocarbons (PAHs) in urban sediments. Recently, the results of forensic analysis have been used to promote a hypothesis that refined tar-based pavement sealers (RT-sealers) are another significant source. To evaluate this hypothesis, a suite of forensic methods was applied to a wider range of PAH data for this study. Sediments PAH profiles are no more similar to RT-sealers than they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Finally, on a double‐ratio plot, samples of lake sediment and sealed parking lot dust from the central and eastern United States grouped together, and apart from 6 other commonly identified urban PAH sources, whereas samples of lake sediment and parking lot dust from the western US plotted in a group distinct from that of central and eastern samples, and closer to the six urban sources. In an earlier publication, O'Reilly et al (), using a different set of ratios, illustrated the same phenomenon (Fig. 2, O'Reilly et al ); their graphical results, as separate from their interpretation of those results, are consistent with the findings of Van Metre et al ().…”
Section: Disclaimersupporting
confidence: 74%
“…Finally, on a double‐ratio plot, samples of lake sediment and sealed parking lot dust from the central and eastern United States grouped together, and apart from 6 other commonly identified urban PAH sources, whereas samples of lake sediment and parking lot dust from the western US plotted in a group distinct from that of central and eastern samples, and closer to the six urban sources. In an earlier publication, O'Reilly et al (), using a different set of ratios, illustrated the same phenomenon (Fig. 2, O'Reilly et al ); their graphical results, as separate from their interpretation of those results, are consistent with the findings of Van Metre et al ().…”
Section: Disclaimersupporting
confidence: 74%
“…In a complex setting with numerous sources that change over time, multiple lines of evidence are required (Boehm ; O'Reilly et al ). Although the focus of this article is receptor models, their use should be part of a broader evaluation that includes considerations of site‐specific history and application of a range of environmental forensic tools (Johnson et al ).…”
Section: Pyrogenic Pah Source Identification—a Particular Challengementioning
confidence: 99%
“…The authors suggested greater similarity between PAHs in sediment samples and RT‐sealed runoff than was observed in either unsealed or petroleum‐asphalt–based sealer in 2 of the double‐ratio plots. Although this was a local study and it ignored the fact that the ratios were within the ranges expected for urban background (Stout et al ), the abstract claimed that these findings indicated that RT‐sealers “may dominate loading of PAHs to urban water bodies in the United States.” To investigate this claim, we used multiple lines of evidence forensic evaluation to consider a wider range of PAH‐affected particles that act as sources to sediments and found that, because of overlapping ranges, diagnostic ratios cannot differentiate among them (O'Reilly et al ). As presented in Mahler et al (), which specific sediment samples were used in the ratio analysis is not clear.…”
Section: Case Study: Are Refined Tar‐based Sealers a Major Source Of mentioning
confidence: 99%
See 2 more Smart Citations